PRAKTIK PEWARISAN PADA MASYARAKAT SUKU MOI DI AIMAS, KECAMATAN AIMAS, KABUPATEN SORONG, PROPINSI PAPUA BARAT - , Christina Rezy R W ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research on the Inheritance Practice in Moi Tribe Community at Aimas, Subdistrict of Aimas, Sorong District, West Papua Province aims to know the cause of girls at the Moi tribe can receive inheritance from their parents and to learn about inheritance practices in the public interest in Aimas Moi. This research is an empirical law research, which is research that promotes field research which aims to obtain primary data. This research uses sampling technique in the form of non-probability sampling, which is not every population has an equal chance to be sampled. Type of sample used is purposive sampling, which is members of the sample specified because it relates to the problem examined. Various data obtained from the results of field research and literature were analyzed qualitatively, the form of intangible explanations numbers or not calculated by describing the data systematically. Based on survey results revealed that: 1. Some of the causes or reasons Moi tribe girls can be inherited his parents' estate, namely the provision of life and a sign of parental affection to their children, as a form of justice in the family, and simplify the girls got a life partner. 2. The process of inheritance to the tribe Moi can be carried out before or after the heir's death, if done after the heir's death, usually done 40 days after the heir's death. Community Moi adopted patrilineal kinship system, then that could be inherited only the male (father), whereas the innate property owned by the wife before marriage (if any) to be community property in the family who later became the estate. Moi inherited property in Interest may be customary land, traditional hamlets, hutam custom, fabric Timor, cassowary bone, full-blooded stones, beads, as well as in social sciences and defend themselves. At the time of division, the heir gathers all family members who became his heir, the husband / wife and children and elders attended local custom. At the meeting, the heir inform all his estate and divide the inheritance to the heirs. Basically, the estate will be divided equally in a fair, as needed, among the heirs by way of deliberation to reach consensus.